Experimental and numerical analysis of thermal performance of shape stabilized PCM in a solar thermal collector. (February 2022) - Yeh, Chung-Yu; Boonk, K.J.F.; Sadeghi, Gholamabbas; Mehrali, Mohammad; Shahi, Mina; Brem, Gerrit; Mahmoudi, Amirhoushang
Abstract: A typical solar domestic water heating system suffers from low energy efficiency due to multiple heat transfer process among components, i.e., the solar thermal collector and the thermal energy storage. In this work, a compact design of storage-integrated solar thermal collector and its compatible phase change material (PCM) storage material were explored. The salt hydrate based composite PCM, the sodium acetate trihydrate (SAT), was used to create a shape stabilized PCM (ssPCMs) for a feasible PCM by its low leakage and high thermal conductivity. The developed ssPCMs has been tested experimentally and a numerical model has been developed to obtain the effective thermal property of the developed ssPCMs by comparing the predicted results with the measurements. Furthermore, the model has been used to study the (dis)charging behavior of PCM in a storage-integrated solar thermal collector which is composed of an evacuated tube and a double spiral coils heat exchanger. A geometrical optimization has been performed to achieve 2.6 times longer of discharging period with a minimum outlet temperature of 55 °C. Moreover, the circulating water is found useful in increasing the PCM charging rate with 9% by transferring the heat from the surface to the center of tube.